Developing Healthcare Service Quality Model Using Servperf Scale: An Application to the Inpatient Department at RSIA Sentosa - Rumintjap, Astrid Felicia; Wandebori, Harimukti (Journal of Business and Management, 2017)
Abstract.Background: With recent investment opportunities in the hospital industry and ever-increasing numbers of private hospitals each year, there is a need for a model on healthcare service quality, applied and tested on the Indonesian market through hospitals, aiming to pin-point areas of service quality shortages. Hence, an empirical study was conducted at a private hospital located in the Bogor regency, West Java.Methods: The study adopted a purposive sampling method to collect responses from 117 inpatients through a self administered questionnaire, then processed through exploratory factor analysis to extract essential factors. Multiple regression and correlation tests were also executed to determine relationships between variables of the study.Results: The result of factor analysis led to the formation of a hospital service quality model for inpatient department that involved 4 main factors translated into; Care Delivery Management, Personnel Performance Characteristics, Doctor-Patient Communication, and Hospital Resources & Infrastructure. The new model also proved to positively impact patient’s overall assessment as whole. Positive relationships were also found between patient’s overall satisfaction with value for money, return intention and recommendation behavior.Conclusion: This study has formulated a hospital service quality model that covers the important factors patients use in evaluating healthcare at the hospital’s inpatient department. It also provides a valid and reliable scale which hospital managers, from equal level of healthcare facility, may reference for future decisions. Keywords: Exploratory Factor Analysis, Hospital Service Quality, Inpatient Department, SERVPERF